Qualidade de vida no trabalho de professores da rede estadual de educação de Minas Gerais - Mendonça, César Henrique de (2016)
The present study was conducted with the main objective of analyzing the perceptions of public basic education and high school teachers in the state of Minas Gerais, Brazil, regarding life quality at work (LQW). In this research, we specifically sought: (a) to characterize the state education network of Minas Gerais; (b) describe socio-demographic characteristics of teachers of the state education network in Minas Gerais, and; (c) describe the indicators of life quality at work of teachers of the state education network of Minas Gerais, from their perception. To conduct this research, the systematic model for understanding LQW described by Vilas Boas and Morin (2015) was used, evaluating the following LQW indicators: sense of the work and sense in the work; psychological well-being and psychological suffering; organizational compromise (emotional and continuous), compromise with the work; workrelated stress; presenteeism and balance between work and private life. An online questionnaire was applied to a sample constituted of 103 teachers from state schools under the responsibility of the Education Superintendence of Campo Belo, Minas Gerais. It was evident that the Systematic Model for understanding life quality at work was efficient in evaluating teacher perception of the public state education network of those participating in this research. It was possible to understand that the LQW involves a set of actions that stimulate a healthy work environment, with the analysis of teacher perception regarding the LQW indicators being an instrument that provides debates, contributing in the prevention of ailments and for the elaboration of personnel management policies. We verified that the teachers that perceive a greater sense in their work present positive aspects in their labor activities and a higher commitment with their work, as well as a stronger relation between work -related stress and psychological suffering, which affect the form in which the teachers perceive work. Analyzing the results, the need for public investment on qualification and valorization of these professionals is clear, in order for the teachers to understand the role they perform within society and to value their work. Even with many challenges, it was possible to verify the sense of satisfaction concerning the teaching profession according to reports presented in this work.